Antibiogram of Bacteria Isolated from Public Toilets - จิตรภิรมย์ กิจจา; สิงหะคเชนทร์ วชิระ (KKU Science Journal, 2014)
Evaluations of antibiotic resistant bacterial contamination in the public toilet in large retail supermarkets, Bangkok by swab method and antibiotic susceptibility was determined by the agar diffusion technique. A total of 186 isolates were colifrom bacteria as Escherichia coli, Klebsiella pneumoniae, Citrobacter spp. and Enterobacter spp. among them, 110, 20, 5 and 3 isolates, and also, 48 Staphylococcus as S. aureus and Staphylococcus spp. are 13 and 35 isolates, respectively. The colifrom bacteria were detected of antibiotic susceptibility with 5 antibiotics; Ampicillin (AMP), Nalidixic acid (NA), Ciprofloxacin (CIP), Gentamicin (CN) and Trimethoprim-sulfamethoxazole (SXT) and Staphylococcus were detected of antibiotic susceptibility with 2 antibiotics; Oxacillin (OX) and Vancomycin (VA). Results, The most colifrom bacteria are resistance to AMP (55.8%) and susceptible to CN (97.8%). Four main groups of antibiogram were found. Resistance to 1 (50.7%) and 2 (4.4%) antibiotics was observed and multidrug resistant colifrom bacteria were showed 3.6 % and they were sensitive to all 5 antibiotic as percentage of 41.3. All of 48 Staphylococcus were sensitive to VA and 8 isolates (16.7%) were resistance to OX. Only 2 (15.4%) from the total of 13 S. aureus belong to Methicillin–resistant Staphylococcus aureus. This study indicated that the risk of antibiotic resistance bacterial infection for the use of public toilets. Therefore, it is important to have relevant knowledge management of public toilets to control the spread of these bacteria.